Antibody Fc engineering for enhanced neonatal Fc receptor binding and prolonged circulation half-life. Issue 7 (3rd October 2019) - Mackness, Brian C.; Jaworski, Julie A.; Boudanova, Ekaterina; Park, Anna; Valente, Delphine; Mauriac, Christine; Pasquier, Olivier; Schmidt, Thorsten; Kabiri, Mostafa; Kandira, Abdullah; Radošević, Katarina; Qiu, Huawei
ABSTRACT: The neonatal Fc receptor (FcRn) promotes antibody recycling through rescue from normal lysosomal degradation. The binding interaction is pH-dependent with high affinity at low pH, but not under physiological pH conditions. Here, we combined rational design and saturation mutagenesis to generate novel antibody variants with prolonged half-life and acceptable development profiles. First, a panel of saturation point mutations was created at 11 key FcRn-interacting sites on the Fc region of an antibody. Multiple variants with slower FcRn dissociation kinetics than the wildtype (WT) antibody at pH 6.0 were successfully identified. The mutations were further combined and characterized for pH-dependent FcRn binding properties, thermal stability and the FcγRIIIa and rheumatoid factor binding. The most promising variants, YD (M252Y/T256D), DQ (T256D/T307Q) and DW (T256D/T307W), exhibited significantly improved binding to FcRn at pH 6.0 and retained similar binding properties as WT at pH 7.4. The pharmacokinetics in human FcRn transgenic mice and cynomolgus monkeys demonstrated that these properties translated to significantly prolonged plasma elimination half-life compared to the WT control. The novel variants exhibited thermal stability and binding to FcγRIIIa in the range comparable to clinically validated YTE and LS variants, and showed no enhanced binding to rheumatoid factor compared to the WT control. These engineered Fc mutants are promising new variants that are widely applicable to therapeutic antibodies, to extend their circulation half-life with obvious benefits of increased efficacy, and reduced dose and administration frequency.